2003
DOI: 10.4269/ajtmh.2003.68.153
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Study on the Efficacy and Safety of Artesunate Suppository in Combination With Other Antimalarials in the Treatment of Severe Malaria in Sudan

Abstract: Abstract. Documentation on the efficacy of artesunate in Africa is limited, and no experience of artesunate use in Sudan is documented. Severe malaria in rural areas of Sudan, where facilities for the safe and effective use of parenteral quinine are lacking, is a frequent problem. Early treatment with artesunate suppositories would provide a simple method for use by unskilled staff and would be an alternative approach to treat malaria in settings with poor resources. We describe a hospital-based study of recta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 13 publications
2
31
0
3
Order By: Relevance
“…artemether, could be suboptimal because of poor absorption (12,25,27,32). Evidence that artesunate suppositories are effective for severe malaria in adults (3,21,22) provided further justification for a trial of rectal artesunate with PNG children with complicated P. falciparum infections. The present study demonstrates the benefits of rectally administered artesunate for the initial treatment of severe malaria in children, with a more rapid fall in parasite density than that observed after i.m.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…artemether, could be suboptimal because of poor absorption (12,25,27,32). Evidence that artesunate suppositories are effective for severe malaria in adults (3,21,22) provided further justification for a trial of rectal artesunate with PNG children with complicated P. falciparum infections. The present study demonstrates the benefits of rectally administered artesunate for the initial treatment of severe malaria in children, with a more rapid fall in parasite density than that observed after i.m.…”
Section: Discussionmentioning
confidence: 99%
“…Artesunate suppositories have been identified by the World Health Organization (WHO) as having great promise, especially for treatment of childhood malaria (34). They have proved safe and efficacious for adults (3,20,22) and in small-scale studies of children with nonsevere infections from Africa (11,19), Southeast Asia (31), South America (10), and Papua New Guinea (PNG) (17). Their pharmacokinetic properties have been characterized previously (5,11,16,19), and maximal plasma drug concentrations, achieved within 1 to 2 h of administration of 10 to 20 mg/kg of body weight, are comparable to those when artesunate at 2 to 4 mg/kg is given by the oral, i.m., or i.v route (16,19).…”
mentioning
confidence: 99%
“…Clinical trials indicated that rectal artesunate (combined with another blood-stage schizonticide) cleared parasitemia more quickly than parenteral quinine and with equal efficacy. 118,119 A global public health threat due to the resurgence of malaria stems from a general collapse of vectorcontrol operations and from resistance to chloroquine or sulfadoxine-pyrimethamine. Recent surveys show rates of treatment failure higher than 50 percent for chloroquine in most affected regions, as well as poor efficacy of sulfadoxine-pyrimethamine in sub-Saharan Africa and Southeast Asia.…”
Section: Mefloquinementioning
confidence: 99%
“…ARTS suppositories have been identified as having great promise, especially for the treatment of pediatric malaria (40). They can be administered when a child cannot take oral therapy and/or when parenteral drug administration is not possible and have proved effective in adults (4,28,29) and children (13,23,25,33) with uncomplicated malaria.…”
mentioning
confidence: 99%